Ecologies of Listening and Presence: Perspectives from a Practitioner. Issue 3 (3rd May 2016) - Paine, Garth
Abstract : After outlining a conceptual and phenomenological framework for my approach to sound I will reflect on how the detritus of anthropocentric sound in our environments, including sounds from everyday devices, may be more consciously considered in terms of general well-being and livability. I will suggest how an acoustic ecology 2.0 approach might be used to rethink sonic design for both environmental and economic benefit. Finally, I will touch on three projects which apply these ideas: (1) the Listen n project which brings together citizen science and creative place-making in national parks and nature preserves of the American Southwest to build nature stewardship and community agency for the conservation of iconic environments, (2) EcoRift, a series of virtual reality experiences that provides youth, mobility-impaired and global communities with access to nature sanctuaries and serves as a scientific archiving system to track environmental change in these sites; and (3) the Psychoacoustic Mapping Project for the Central Arizona Long-Term Environmental Monitoring initiative.